2005
DOI: 10.1007/s10750-005-4142-1
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties and Light Climate in Lake Verevi

Abstract: The optical properties and light climate during the ice-free period in the highly stratified Lake Verevi (Estonia) have been studied together with other lakes in same region since 1994. The upper water layer above the thermocline belongs to class ''moderate'' by optical classification of Estonian lakes but can turn ''turbid'' (concentration of chlorophyll a up to 73 mg m )3 and total suspended matter up to 13.2 g m )3 ) during late summer blooms. In the blue part of the spectrum, light is mainly attenuated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In the mainly anaerobic hypolimnetic layer the bacterial number was strongly correlated (partial r > 0.80, p < 0.01) to the concentration of total nutrients (N, P) and phosphate, but not with the inorganic nitrogen. A strong correlation was also found Shaded area on the plot shows the part of water-column below the light attenuation of 1% (z 1% ) (Reinart et al, 2005) at mid-day (12:00).…”
Section: Relationships Between Bacterioplankton With Other Biota and mentioning
confidence: 60%
“…In the mainly anaerobic hypolimnetic layer the bacterial number was strongly correlated (partial r > 0.80, p < 0.01) to the concentration of total nutrients (N, P) and phosphate, but not with the inorganic nitrogen. A strong correlation was also found Shaded area on the plot shows the part of water-column below the light attenuation of 1% (z 1% ) (Reinart et al, 2005) at mid-day (12:00).…”
Section: Relationships Between Bacterioplankton With Other Biota and mentioning
confidence: 60%
“…Although Reinart et al (2005) observed a pronounced seasonality of the limnological features in an Estonian lake, time was not considered in the generation of models correlating k and SD. In our study, the effects of time depended on the ecosystem considered.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon occurred only when the water column was illuminated. According to our measurements (see also Reinart et al, 2005), in L. Verevi only 1% of light penetrates generally down to 3.5-5.5 m and our intermediate trap was placed at the depth of 5 m. Despite the great variability of incident irradiance, the exponential light extinction was in all cases very similar.…”
Section: Nutrients In the Sediment Trapsmentioning
confidence: 57%
“…Description of lake , its environmental properties and peculiar partial meromixis in 2000 and 2001 is described in different articles of present issue Reinart et al, 2005;Ko˜iv & Kangro, 2005;No˜ges & Solovjova, 2005;No˜ges, 2005).…”
Section: Methodsmentioning
confidence: 99%